Effects of High-Volume Versus High-Load Resistance Training on Skeletal Muscle Growth and Molecular Adaptations - Vann, Christopher G.; Sexton, Casey L.; Osburn, Shelby C.; Smith, Morgan A.; Haun, Cody T.; Rumbley, Melissa N.; Mumford, Petey W.; Montgomery, Nathan T.; Ruple, Bradley A.; McKendry, James; Mcleod, Jonathan; Bashir, Adil; et al. (Frontiers in Physiology, 2022)
We evaluated the effects of higher-load (HL) versus (lower-load) higher-volume (HV) resistance training on skeletal muscle hypertrophy, strength, and muscle-level molecular adaptations. Trained men (n=15, age: 23±3 y; training experience: 7±3 y) performed unilateral lower body training for 6 weeks (3x weekly), where single legs were randomly assigned to HV and HL paradigms. Vastus lateralis (VL) biopsies were obtained prior to study initiation (PRE) as well as 3 days (POST) and 10 days following the last training bout (POSTPR). Body composition and strength tests were performed at each testing session, and biochemical assays were performed on muscle tissue after study completion. Two-way within subjects repeated measures ANOVAs were performed on most dependent variables, and tracer data was compared using dependent samples t-tests. A significant interaction existed for VL muscle cross-sectional area (assessed via magnetic resonance imaging; interaction p=0.046), where HV increased this metric from PRE to POST (+3.2%, p=0.018) whereas HL training did not (-0.1%, p=0.475). Additionally, HL increased leg extensor strength more so than HV training (interaction p=0.032; HV